Creative teacher in Polish diaspora education: Examples from school practice - Kasprzak, Michalina (Adam Mickiewicz University Poznan, 2024)
The article presents the basic assumptions concerning the teachers’s creative role in the education of the Polish community abroad based on selected Saturday schools across Spain, Iceland, Turkey, and Italy. It highlights the importance of the activities of Polish schools in bilingual and multilingual environments in the contemporary world. The article describes selected examples of activities conducted with preschool and early school-age students from the school practice of six institutions. It also emphasizes the importance of teachers’ experiences in inspiring students and parents to collab orate on projects and engage with Polish communities in Poland and abroad. The article underscores the idea of cooperation between Polish and Polish diaspora institutions in supporting teachers’ com petences for educating young children. Artykuł przedstawia podstawowe założenia dotyczące twórczej roli nauczycieli w edukacji polskiej społeczności za granicą na przykładzie wybranych szkół sobotnich w Hiszpanii, Islandii, Turcji i Włoszech. Podkreśla znaczenie działalności polskich szkół w środowiskach dwujęzycznych i wielojęzycznych we współczesnym świecie. Artykuł opisuje wybrane przykłady działań prowadzonych z dziećmi w wieku przedszkolnym i wczesnoszkolnym w ramach praktyki sześciu placówek. Zwraca również uwagę na rolę doświadczeń nauczycieli w inspirowaniu uczniów i rodziców do współpracy przy projektach oraz zaangażowania w życie polskich społeczności w Polsce i za granicą. Podkreślono ideę współpracy pomiędzy instytucjami polskimi a instytucjami polonijnymi w zakresie wspierania kompetencji nauczycieli w edukacji małych dzieci.